Religious Cultural-based Educational Model Through Mentoring to Form Islamic Humanistic Values - Abdullah, Muhammad Luthfi; Nila Praja, Handayani; Mahendra, Diana; Busro, Busro (ISTAWA, 2020)
The problem challenge in Education in Indonesia is actions that decrease human dignity. One of them is corruption that becomes a big agenda to be fought in this country. Besides, sexual abuse to children also needs to be taken care of. That is why efforts to return humanistic values are required to be alternatives in education. Consent and planned knowledge which tries to restore human dignity can be formed through culture. Mentoring program is one of the activities that can be used in developing religious culture. This research was aimed to: find out how humanistic and spiritual cultural-based education model is employed through mentoring, and find out how the education model influences humanistic values. This research employed a mixed method. The mixed-method design used is a sequel exploratory design. The research subjects are integrated internship students of Universitas 17 Agustus 1945 Cirebon. The results of this research showed that; there were three activities as results of mentoring that described humanistic and religious cultural-based education model, those are physical development, social service, and public work for the environment; those three activities gave positive influences towards the forming of humanistic values.Tantangan masalah dalam pendidikan di Indonesia adalah tindakan yang menurunkan martabat manusia. Salah satunya adalah korupsi yang menjadi agenda besar untuk diperangi di negeri ini. Selain itu, pelecehan seksual kepada anak-anak juga perlu diperhatikan. Oleh karena itu diperlukan upaya untuk mengembalikan nilai-nilai humanistik sebagai alternatif dalam pendidikan. Persetujuan dan pendidikan terencana yang mencoba mengembalikan martabat manusia dapat dibentuk melalui budaya. Program pendampingan adalah salah satu kegiatan yang dapat digunakan dalam mengembangkan budaya agama. Penelitian ini bertujuan untuk mendeskripsikan bagaimana model pendidikan berbasis budaya humanistik dan agama dilakukan melalui pendampingan, dan mendeskripsikan bagaimana model pendidikan mempengaruhi nilai-nilai humanistik. Penelitian ini menggunakan metode campuran. Desain metode campuran yang digunakan adalah desain eksplorasi sequal. Subjek penelitian adalah mahasiswa magang terintegrasi Universitas 17 Agustus 1945 Cirebon. Hasil penelitian ini menunjukkan bahwa ada tiga kegiatan sebagai hasil pendampingan yang menggambarkan model pendidikan berbasis budaya humanistik dan agama, yaitu pengembangan fisik, pelayanan sosial, dan pekerjaan bersama untuk lingkungan; ketiga kegiatan tersebut memberikan pengaruh positif terhadap pembentukan nilai-nilai humanistik.